Impact of Pitcher Irrigation and Mulching on the Summer Season (Jethwi) Lac Crop Sustainability and Pruning Response on Ber (Ziziphus mauritiana) - Singh, R. K.; Mishra, Y. D.; Babo, Bangali (Indian Forester, 2010)
No abstract